2003
DOI: 10.1029/2002jd002713
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic polar stratospheric clouds under temperature perturbation by nonorographic inertia gravity waves observed by micropulse lidar at Syowa Station

Abstract: 1] Type II polar stratospheric clouds (PSCs) were observed by micropulse lidar (MPL) at Syowa Station in the Antarctic on 30 June and on 1 July 2001. The vertical profiles of the PSCs had a wavy structure that was synchronized with the temperature fluctuations. A wave analysis using radiosonde data shows that the wavy fluctuations were associated with an inertia gravity wave that was not forced by ground topography, but probably by a spontaneous adjustment in association with synoptic-scale wave-breaking proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 22 publications
1
65
0
Order By: Relevance
“…Case studies of mountain waves induced by the Scandinavian Mountains showed that the waves can cause localized cooling of up to 10-15 K (Carslaw et al, 1998b;Dörnbrack et al, 1999Dörnbrack et al, , 2002. The Antarctic Peninsula is another well-known hot spot for the formation of PSCs from mountain waves in the Southern Hemisphere (Wu and Jiang, 2002;Shibata et al, 2003;Höpfner et al, 2006b;Baumgaertner and McDonald, 2007;Eckermann et al, 2009;Orr et al, 2015). In the Antarctic polar stratosphere, waveinduced PSC formation is particularly important in fall or spring, whereas synoptic-scale temperatures in winter are usually well below the PSC formation threshold (Campbell and Sassen, 2008;McDonald et al, 2009;Noel and Pitts, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies of mountain waves induced by the Scandinavian Mountains showed that the waves can cause localized cooling of up to 10-15 K (Carslaw et al, 1998b;Dörnbrack et al, 1999Dörnbrack et al, , 2002. The Antarctic Peninsula is another well-known hot spot for the formation of PSCs from mountain waves in the Southern Hemisphere (Wu and Jiang, 2002;Shibata et al, 2003;Höpfner et al, 2006b;Baumgaertner and McDonald, 2007;Eckermann et al, 2009;Orr et al, 2015). In the Antarctic polar stratosphere, waveinduced PSC formation is particularly important in fall or spring, whereas synoptic-scale temperatures in winter are usually well below the PSC formation threshold (Campbell and Sassen, 2008;McDonald et al, 2009;Noel and Pitts, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic stratospheric vortex is generally warmer and more disturbed due to planetary wave activity, possibly making gravity waves an even more important source of PSCs in the Northern Hemisphere . Although most case studies focus on gravity waves from orographic sources, Hitchman et al (2003) and Shibata et al (2003) showed that non-orographic gravity waves can also trigger PSC formation.…”
Section: Introductionmentioning
confidence: 99%
“…Using Challenging Mini-Satellite Payload (CHAMP) radio occultation observations, McDonald et al (2009) show that gravity waves increase the frequency of temperatures below T NAT in June in the Antarctic, in particular around the Antarctic Peninsula, which is known as a mountain wave "hotspot". Shibata et al (2003) pointed out that non-orographic gravity waves generated by spontaneous adjustment which is related to synoptic-scale wave breaking also have an impact on the formation of ice particles. This result indicates that the impact of gravity waves is not restricted to above high mountains.…”
Section: Introductionmentioning
confidence: 99%
“…PSCs containing high number densities of NAT can act as mother clouds for extremely large NAT particles (so called "NAT rocks") (Fahey et al, 2001;Fueglistaler et al, 2002). These rock particles efficiently remove HNO 3 from the lower stratosphere with their large sedimentation velocity (Fahey et al, 2001;Shibata et al, 2003). The NAT formation temperature (T NAT ) is derived by Hanson and Mauersberger (1988), and although dominant nucleation mechanisms remain uncertain and controversial (Lowe and MacKenzie, 2008), the correlation coefficient between the potential PSC volumes using T NAT and the Arctic ozone depletion is more than 0.9 (Rex et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Older versions than the MPL-4 have already been deployed in two other Antarctic stations (see Fig. 1): Syowa (Japan, 69.0 • S 39.5 • E), where a PSC type-II single event was reported and attributed to low temperature fluctuations related to inertia gravity waves (Shibata et al, 2003) and remaining usually outside the polar vortex (see Fig. 1 version 3) with careful smoothing procedures (Campbell and Sassen, 2008).…”
Section: Introductionmentioning
confidence: 99%